A4.3 Differences of bone WNT regulators expression between fragility fractures and osteoarthritis patients. (31st January 2014) - Rodrigues, AM; Caetano-Lopes, J; Oliveira, V; Vidal, B; Gonçalves, MJ; Sepriano, A; Sarmento, M; Monteiro, J; Fonseca, JE; Canhão, H
Abstract : Introduction: The importance of Wnt signalling, a crucial pathway for osteoblast differentiation and a master bone mass regulator as been recently highlighted. With this study, we aim to compare bone expression of Wnt regulators between fragility fracture and osteoarthritis patients. Methods: Patients submitted to total hip replacement surgery either due to a fragility fracture or to osteoarthritis, at the Orthopedics department of Hospital de Santa Maria, were recruited. Clinical risk factors (CRFS) for osteoporotic fractures were collected. RNA was extracted from a small trabecular bone sample and analysed by quantitative real-time protein chain reaction (RT-PCR). Immunohistochemistry analysis for DKK1 and SOST was also performed. Results: 118 patients submitted to total hip replacement surgery, 55 due to fragility fracture, were evaluated. Fragility fracture patients were predominantly women (84% vs 49%, p<0.001), significantly older (80 ± 7 vs 68 ± 12, p < 0.001) and had significantly more previous fragility fractures than the osteoarthritis group (33% vs 5%, p < 0.001). Univariate analysis showed that RANKl/OPG ratio, a marker of osteoclastogenisis, was significantly higher in the fragility fracture group (p < 0.001). On the other hand osteocalcin expression, a marker of osteoblast maturation was significantly lower in fragility fracture group (p < 0.001). Regarding Wnt regulators, WNT 10b (β = -0, 398, p < 0.001) and DKK1 (β = -0, 387, p < 0.001) expression was significantly higher in osteoarthritis group even after adjusting for age and gender. In multivariate analysis SOST (β = 0.236, p = 0.0411) was significantly higher in the fragility fracture group. Semi-quantitative analysis of immunohistochemistry results for DKK1 revealed a significantly higher staining scores (p = 0.04) in the osteoarthritis group. Conclusion: In fragility fracture patients, bone SOST expression is upregulated. In osteoarthritis patients, DKK1 gene expression and protein staining is significantly higher than in fragility fractures. These results improve the knowledge of WNT disturbances in these two diseases and can be of help to identify new treatment targets.